CONSUMER PREFERENCES ON NEW CHILLI VARIETIES OF BENGKULU UNIVERSITY - Arianti, Nyayu Neti; Ganefianti, Dwi Wahyuni; Sutrawati, Mimi (Jurnal AGRISEP, 2019)
This research was conducted to 1) Analyze the perception of consumers on the attributes of chili, and 2) Know which chili products are selected by consumers based on shape,  size and which are most wanted to buy. Forty consumer respondents were taken by accidental sampling technique.  Consumers are asked to assess 10 types of the UNIB chili varieties, both monoculture and combination polyculture between varieties. The results showed that the majority of respondents stated that the size and shape attributes were important as the basis for the decision to buy chili, while the attributes of uniform size and shape are considered normal.  The variety of chili which consumers like because of their size, shape and desire to be purchased were UNIB C H13. While for this type of combination, the combination of UNIB C H13 and UNIB C H53 is desired to be purchased by consumers. This type of combination should be cultivated by farmers because it is resistant to pests, high productivity and preferred by consumers.